2016
DOI: 10.1002/jctb.5024
|View full text |Cite
|
Sign up to set email alerts
|

Construction and optimization of trans‐4‐hydroxy‐L‐proline production recombinant E. coli strain taking the glycerol as carbon source

Abstract: BACKGROUND: Trans-4-hydroxy-L-proline (Hyp) is a value-added amino acid that is an applicable chiral building block in some industries, such as the pharmaceutical, cosmetic and healthcare industries. Given that glycerol is a good carbon source for microbial fermentation and a large amount of glycerol is produced by the biodiesel industry, this study investigated a value-added Hyp fermentation from glycerol using an engineered Escherichia coli strain. RESULTS: By optimizing the proline-4-hydroxylase (P4H) gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The highest t 4Hyp production to date was 54.8 g/L at 60 h using integrated system engineering in E. coli without L-proline addition in a 7.5-L bioreactor , in which the deletion of putA , proP , putP , and aceA , and the mutation of proB contributed to l -proline and relieved its feedback inhibition, and a tunable circuit based on quorum sensing for the dynamic regulation of ODHC activity and rationally designed l -proline hydroxylase [ 69 ]. t 4Hyp production using proline 4-hydroxylase with chemo-physical combination mutagenesis, taking glycerol as the carbon source, and optimizing the fermentation medium(tryptone, FeSO 4 , l -proline) with single-factor, Plackett–Burman, steepest ascent, and a central composite design experiment, was achieved at 25.4 g/L of t 4Hyp [ 81 ]. Subsequently, Zhao et al attained a t 4Hyp concentration of 14.4 g/L by integrating the Vitreoscilla hemoglobin gene ( vgb ) into recombinant E. coli expressing proline 4-hydroxylase in fed-batch fermentation in a 1.4-L bioreactor after 57 h of cultivation [ 75 ].…”
Section: Metabolic Engineering Of Trans -4-hydroxy- L -Proline Production In a Bioreactormentioning
confidence: 99%
“…The highest t 4Hyp production to date was 54.8 g/L at 60 h using integrated system engineering in E. coli without L-proline addition in a 7.5-L bioreactor , in which the deletion of putA , proP , putP , and aceA , and the mutation of proB contributed to l -proline and relieved its feedback inhibition, and a tunable circuit based on quorum sensing for the dynamic regulation of ODHC activity and rationally designed l -proline hydroxylase [ 69 ]. t 4Hyp production using proline 4-hydroxylase with chemo-physical combination mutagenesis, taking glycerol as the carbon source, and optimizing the fermentation medium(tryptone, FeSO 4 , l -proline) with single-factor, Plackett–Burman, steepest ascent, and a central composite design experiment, was achieved at 25.4 g/L of t 4Hyp [ 81 ]. Subsequently, Zhao et al attained a t 4Hyp concentration of 14.4 g/L by integrating the Vitreoscilla hemoglobin gene ( vgb ) into recombinant E. coli expressing proline 4-hydroxylase in fed-batch fermentation in a 1.4-L bioreactor after 57 h of cultivation [ 75 ].…”
Section: Metabolic Engineering Of Trans -4-hydroxy- L -Proline Production In a Bioreactormentioning
confidence: 99%
“…Given the influence of such variables as pretreatment temperature, pretreatment time, acetic acid concentration (v/v), and H 2 SO 4 addition (w/v), the AAO pretreatment was optimized with a series of experiments of a Plackett–Burman design (PBD), a steepest ascent design and a central composite design [39, 40]. The most prominent parameters and the optimal concentrations domain were tested using a Plackett–Burman design (Additional file 1: Table S1) and a steepest ascent experiment, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…l-Pro production in HYP2M was eventually decreased to a final concentration of 0.2 g liter −1 in 60 hours. Park et al (5,30) reported that recombinant E. coli with datp4h catalyzed 4-Hyp with l-Pro as substrate in a yield of 25 g liter −1 , with glycerol and glucose (41 g liter −1 ) as carbon sources, respectively. Compared with previous results, our reported 4-Hyp production method gave the highest yield.…”
Section: Efficient Production Of 4-hyp By Genome Mining and Rational mentioning
confidence: 99%